Over‐expression of hsa_circ_0000116 in patients with non‐obstructive azoospermia and its predictive value in testicular sperm retrieval. (28th August 2020) - Lv, Mo‐qi; Zhou, Liang; Ge, Pan; Li, Yi‐xin; Zhang, Jian; Zhou, Dang‐xia
Abstract: Background: Non‐obstructive azoospermia (NOA), identified in approximately 10% of infertile males, is a multifactorial disease whose molecular mechanisms remain unknown. Objectives: The aim of this study was to identify the role of hsa_circ_0000116 in NOA and illustrate its predictive value in testicular sperm retrieval. Materials and methods: The study included 78 individuals, 58 with NOA and 20 with obstructive azoospermia (OA). Serum hormones including testosterone (T), follicle‐stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), and estradiol II (E2) were measured. Testicular histopathology was analyzed by at least two pathologists. The expression of hsa_circ_0000116 in testicular tissue samples was detected using real‐time PCR, and the circRNA‐miRNA‐mRNA networks were predicted using bioinformatics analysis. Results: Our study illustrated that the expression of hsa_circ_0000116 was significantly higher in testicular tissue samples of NOA patients than in that of OA patients. Moreover, hsa_circ_0000116 was aberrantly expressed in three different pathological types of NOA: It was significantly up‐regulated in patients with Sertoli cell–only syndrome (SCOS) when compared to patients with hypospermatogenesis (HS). In addition, the expression of hsa_circ_0000116 was negatively correlated with Johnsen score, while it was positively correlated with serum FSH level. A multivariate logistic regression model demonstrated that a high level of hsa_circ_0000116 was associated with a low rate of successful testicular sperm retrieval. Bioinformatics analysis and verification experiments showed that one of the most probable potential target miRNA for hsa_circ_0000116 was hsa‐miR‐449a. Further analysis indicated that hsa_circ_0000116 may be affecting the fertility function through a hsa_circ_0000116‐miR‐449‐autophagy‐related competing endogenous RNA (ceRNA) network. Discussion and conclusion: We report for the first time that hsa_circ_0000116 may play pivotal roles in regulating spermatogenesis and may also be a potential biomarker for the diagnosis and treatment of NOA, while acting as a predictive tool for the rate of successful testicular sperm retrieval in NOA patients.